Microstomum (Platyhelminthes, Macrostomorpha, Microstomidae) from the Swedish west coast: two new species and a population description - Atherton, Sarah; Jondelius, Ulf (European Journal of Taxonomy, 2018)
Two new species of marine Platyhelminthes, Microstomum laurae sp. nov. and Microstomum edmondi sp. nov. (Macrostomida: Microstomidae) are described from the west coast of Sweden. Microstomum laurae sp. nov. is distinguished by the following combination of characters: rounded anterior and posterior ends; presence of approximately 20 adhesive papillae on the posterior rim; paired lateral red eyespots located level with the brain; preoral gut extending anterior to brain and very small sensory pits. Microstomum edmondi sp. nov. is a protandrous hermaphrodite with a single ovary, single testis and male copulatory organ with stylet. It is characterized by a conical pointed anterior end, a blunt posterior end with numerous adhesive papillae along the rim, and large ciliary pits. The stylet is shaped as a narrow funnel with a short, arched tip. In addition, the first records of fully mature specimens of Microstomum rubromaculatum von Graff, 1882 from Fiskebäckskil and a phylogenetic analysis of Microstomum Schmidt, 1848 based on the mitochondrial cytochrome oxidase I (COI) gene are presented.